Serving with Values in Challenging Times: Exploring Institutional Leaders' Values Work at Local Level During COVID-19 (Lex localis - Journal of Local Self-Government, 2024)
While existing literature mostly analyzes public leaders' pandemic responses, limited attention has been paid to local government leaders in terms of values work. This study examines the values created and infused by senior managers who serve as institutional leaders in local governments during the COVID-19 pandemic. Focusing on the data collected from the responses of the sample set, the study aims to illuminate the processes of creating and infusing values among senior managers of a metropolitan municipality in Türkiye. For this aim, interviews were conducted with 11 senior managers of this metropolitan municipality. The findings produced within the scope of two propositions firstly reveal three types of value created for, and infused into the organization: personal, organizational, and service-related. Secondly, the study identifies the uniform process devoted to values work among senior managers and reveals that there are no significant differences in the styles of creating and infusing values (i.e., values work) among managers at different levels of local government in challenging times.